Critical Thinking and Collaboration Skills in Catholic Religious Education: A Study of Junior High School Students - Wahnyuningrum, Paulina Maria Ekasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The aims of this research is to find out the critical thinking and collaboration skills of the junior high students in catholic religious subjects. This is a quantitative approach with a descriptive method.The research population were the eighth students of junior high school in Palangkaraya, totaling 35 students. The research instrument used 8 questions for critical thinking skill and 8 questions for collaboration skill. The collected data analyzed using the descriptive analysis. The results of the analysis show that the critical thinking and collaboration of the students are in the middle criteria. Some reasons can be concluded such as teachers' lack of ability to integrate learning that leads to critical and collaborative thinking, monotonous learning activities and the lack of familiarity with religious learning being made into arguments and discussions.